Two novel iridoid derivatives isolated from Phlomis likiangensis. Issue 11 (14th March 2018) - Li, Xiao-Hui; Lu, Li-He; Li, Xu-Hong; Li, Yun-Biao; Duan, Yuan-Chang; Fu, De-Huan; Mei, Shuang-Xi; Cui, Tao; Wang, Jing-Kun; Zhu, Zhao-Yun
Graphical abstract: Highlights: Two new iridoid derivatives were isolated and structural elucidated. Phloloside H (1 ) was a rare 4′-substituted iridoid glycoside, contained a carbonate ester substituent group. Phloline (2 ) was a novel normonoterpene. Phloline (2 ) was probably derived from iridoids, and we suggested its biosynthetic pathway. All isolated compounds' cytotoxic, antibacterial and antioxidative activities were tested. Abstract: The extract of the aerial and underground parts of Phlomis likiangensis afforded two new iridoid derivatives, namely as phloloside H (1 ) and phloline (2 ), along with four known compounds (3 –6 ), and compound2 was a novel normonoterpene. Their structures were elucidated on the basis of spectroscopic studies and chemical methods. Six compounds were assayed for cytotoxic, antibacterial and antioxidative activities, but were either inactive or very weakly active.